Optimasi Kecepatan Pengadukan pada Biosorpsi Methyl Orange Menggunakan Kulit Lengkeng Termodifikasi Putih Telur Itik - Putri Aulia Pratiwi; Desy Kurniawati (Lembaga Yasin AlSys, 2026)
Although various lignocellulosic biomasses have been developed as biosorbents for dye removal, the use of longan peel modified with duck egg white for Methyl Orange biosorption, particularly in relation to the effect of agitation speed, remains limited. This study aimed to determine the optimum agitation speed for Methyl Orange biosorption using longan peel modified with duck egg white in a batch system. The study employed a quantitative approach with a laboratory experimental design. The characteristics of the biosorbent were analyzed using Fourier-transform infrared (FTIR) spectroscopy, while the Methyl Orange concentration was determined using a UV–Vis spectrophotometer. The results showed that agitation speed affected biosorption performance. The optimum condition was achieved at 200 rpm, with the highest adsorption capacity of 66.47 mg/g. FTIR analysis confirmed the successful modification of the biosorbent through the addition of protein functional groups to the longan peel surface. The FTIR spectrum after biosorption also showed the presence of sulfonate (S=O) groups, indicating the adsorption of Methyl Orange. These findings demonstrate that protein modification and an appropriate agitation speed can enhance the performance of lignocellulosic biomass-based biosorbents in adsorbing anionic dyes. This study contributes to the development of potentially environmentally friendly and low-cost biosorbents for wastewater treatment and provides a basis for optimizing the biosorption process. Future research should investigate adsorption kinetics and isotherms, biosorbent regeneration, and its application to actual industrial wastewater.